2010
DOI: 10.4049/jimmunol.1000906
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-Inflammatory Drugs Increase TNF Production in Rheumatoid Synovial Membrane Cultures and Whole Blood

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 56 publications
8
41
1
Order By: Relevance
“…It was shown that celecoxib increases TNF-a production in LPS-stimulated human monocytes, in human RA synovial membranes cultures, and in whole blood of human subjects following celecoxib treatment in vivo (48), which is in concordance with our results. In the present study, TNF-a blockade has no suppressive effects on PGE 2 and IL-17A production in Th17-RASF cultures.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It was shown that celecoxib increases TNF-a production in LPS-stimulated human monocytes, in human RA synovial membranes cultures, and in whole blood of human subjects following celecoxib treatment in vivo (48), which is in concordance with our results. In the present study, TNF-a blockade has no suppressive effects on PGE 2 and IL-17A production in Th17-RASF cultures.…”
Section: Discussionsupporting
confidence: 93%
“…Because PGE 2 is produced in many inflammatory diseases, the mechanism reported in the present study may be important in other Th17-mediated autoimmune diseases in which Th17 cells are implicated, including psoriasis, multiple sclerosis, and inflammatory bowel disease (8,9). The induction of TNF-a in the Th17-RASF cultures by celecoxib may explain why the inhibition of COX-2 activity reduces joint pain and improves motility in humans, but does not inhibit disease progression (48). Future research should carefully address whether the inducing effect of celecoxib on TNF-a can be compensated with anti-TNF-a treatment in vivo.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Such an unusual differentially regulated IL-6 down-and TNF-α upregulation was already described by Tsuboi et al, who observed this phenomenon after treating human PBMCs with nonsteroidal anti-inflammatory drugs (NSAIDs) [50]. In another study increased levels of TNF-α after NSAID treatment were directly attributed to a reduced level of prostaglandin E2 that, although mostly regarded as a proinflammatory mediator, also possesses potent antiinflammatory properties [51]. Further study is necessary to examine, if similar mechanisms could be responsible for the effect of VALE and OA.…”
Section: Discussionsupporting
confidence: 59%
“…75 The major mechanism of action of NSAIDs was found to be the inhibition of PG synthesis, through inhibition of COXs, that is to say preventing the AA from forming PG. [76][77][78] it has a very short half-live in blood, its oxidization to 15-ketoprostaglandins is catalyzed by 15-hydroxyprostaglandin dehydrogenase In order to design any structure with pyrrole moiety or its fused form indole, vital considerations must be taken to ensure its anti-inflammatory activity. 32,74,79,80 First, the structure should consist of an acidic moiety (carboxylic acid, enols, ester etc.)…”
Section: Structure-activity Relationships (Sar)mentioning
confidence: 99%